Breaking Barriers or Reinforcing Gaps? Gender Wage Disparities Across Skill Levels in a Developing Economy - Zubaria Andlib (Global Labor Organization (GLO), 2025)
Many factors are behind the persistent gender wage gap in a developing economy, such as occupational segregation, social norms, and gender attitudes. To narrow the gender wage gap, it is mandatory to create gender-inclusive work environments, increase minimum wages and implement labour market regulations. The present study investigates the gender wage gap for four occupational groups based on skill levels as per ISCO-8 guidelines in the case of a developing economy, Pakistan. This research has utilised the latest available Labour Force Survey (2020-21) data and applied the Oaxaca-Blinder decompositions and unconditional quantile regressions. The empirical outcome described that women earn lower wages in low and average-skilled occupations; however, in high and very-high-skilled occupations, women are in advantageous positions. In addition, the empirical estimation elaborates on the presence of glass ceiling effects in low, average, and very high-skilled occupations in Pakistan. To tackle the issue of the gender wage gap, governments, employers, and society must undertake a collective effort to achieve equal pay for equal work and provide adequate career opportunities in high-skilled occupations for women in developing economies.
Keywords: J08; J24; J31; 330; Gender wage gap; skill levels; occupations; glass ceiling